2016
DOI: 10.3171/2016.1.spine151199
|View full text |Cite
|
Sign up to set email alerts
|

The use of lumbar drains in preventing spinal cord injury following thoracoabdominal aortic aneurysm repair: an updated systematic review and meta-analysis

Abstract: OBJECTIVE Paraplegia and paraparesis following aortic aneurysm repair occur at a substantially high rate and are often catastrophic to patients, their families, and the overall health care system. Spinal cord injury (SCI) following open thoracoabdominal aortic aneurysm (TAAA) repair is reported to be as high as 20% in historical controls. The goal of this study was to determine the impact of CSF drainage (CSFD) on SCI following TAAA repair. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 46 publications
2
46
0
Order By: Relevance
“…125 To date, evidence is insufficient for a recommendation to use prophylactic MEP and/or cerebrospinal fluid (CSF) pressure monitoring and drainage in aortic arch repair with the use of FET. 125,126 However, the use of lumbar CSF pressure monitoring and drainage may be considered based on individualized risk assessment for spinal cord ischaemia. 127,128 In situations of delayed SCI, selective secondary insertion of drainage as part of a treatment bundle is recommended.…”
Section: Spinal Cord Perfusion Pressure Monitoring and Lumbar Cerebromentioning
confidence: 99%
See 1 more Smart Citation
“…125 To date, evidence is insufficient for a recommendation to use prophylactic MEP and/or cerebrospinal fluid (CSF) pressure monitoring and drainage in aortic arch repair with the use of FET. 125,126 However, the use of lumbar CSF pressure monitoring and drainage may be considered based on individualized risk assessment for spinal cord ischaemia. 127,128 In situations of delayed SCI, selective secondary insertion of drainage as part of a treatment bundle is recommended.…”
Section: Spinal Cord Perfusion Pressure Monitoring and Lumbar Cerebromentioning
confidence: 99%
“…127,128 In situations of delayed SCI, selective secondary insertion of drainage as part of a treatment bundle is recommended. 126,129 As imaging is still not able to provide us with a detailed description of intraspinal collateralization, which might be the answer to who is at increased risk for SCI, risk prediction models remain approximations, e.g. the collateral network concept and, developed on that basis, the 4-territory concept.…”
Section: Spinal Cord Perfusion Pressure Monitoring and Lumbar Cerebromentioning
confidence: 99%
“…7 In 2015, the European Association for Cardiothoracic Surgery similarly recommended CSF drainage for TAAA repair for patients at high risk for SCI. 8 Although randomized controlled studies showed benefit for CSF drainage in open TAAA repair, 9 its routine use in TEVAR procedures remains uncertain and a topic of considerable debate . 8, 10, 11 …”
Section: Introductionmentioning
confidence: 99%
“…4 A recent systematic review found that CSF drainage decreased early SCI by nearly half; however, these findings were not consistent in delayed or late SCI. 5 At present, no firm conclusions can be drawn with regard to the role of CSF drainage in endovascular aortic procedures. The potential benefits of CSF drainage also need to be considered in the context of tangible complications associated with this intervention.…”
mentioning
confidence: 99%
“…The potential benefits of CSF drainage also need to be considered in the context of tangible complications associated with this intervention. 5 Recently, Rong et al 6 reported that CSF drainageÀrelated complications occur in 6.5% of patients. The most common adverse events included bloody CSF, headache, and subarachnoid hemorrhage.…”
mentioning
confidence: 99%